Abortive and transforming infection of rat cell line 3Y1 by adenovirus type 12. - Hama, S (1978)
Human adenovirus type 12 underwent an abortive and transforming infection in clonal cultures of rat cell line 3Y1. The frequency of transformation was proportional to the dose of input virus. The ratio of PFU to transforming units was 1.1 X 10(5).